Evaluasi Pemantauan Intrapartum pada Persalinan dengan BBLR di RSUD Gunung Jati Kota Cirebon - Lisnawati Lisnawati (Jurnal Kesehatan, 2017)
Low Birth Weight (LBW) is neonates with birth weight less than 2,500 grams (up to 2,499 grams) without looking the duration of pregnancy. LBW is one cause of infant mortality rate in Indonesia. Increasing the knowledge, attitudes, and skills of midwives are the strategy to reduce infant mortality rate. The number of spontaneous labor with preterm gestation by midwives is the main reason to increase the skills of the LBW. This study was aimed to evaluate the skills of midwives in the management of labor with low birth weight in intrapartum monitoring. The methods were a quantitative and qualitative study with cross sectional approach. The quantitative was to evaluate the skills of midwives in intrapartum monitoring (active phase of the first stage), it is using checklists to 20 midwives in the delivery room who had received at least 1 case of labor with LBW. Research also conducted qualitatively by interviewing midwives in the delivery room and hospital managers. The results of this study showed that the midwives were not competent in the intrapartum monitoring of LBW. The average value of midwives skills in action intrapartum monitoring is 70.3% (the highest value is 81,25% and the lowest is 62,25%). The midwives know that labor with LBW is not authorized by midwives, all this time management labor with low birth weight is through a doctor's advice, but the midwives were not competent and not confident in providing care in the management of labor with LBW. This study showed that the skills of midwives in the intrapartum monitoring of LBW are not good enough to be able to reduce mortality due to LBW.